The Role of the Depok City Environmental Agency in Promoting National Defense - Suwarsit Suwarsit (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Development across various sectors should not be solely focused on increasing income but must also consider its environmental impact to ensure sustainability. In this regard, the role of the community is crucial as a key factor in preserving and conserving the environment. This study emphasizes that community groups possess the awareness and responsibility to participate in environmental conservation as an expression of love for the homeland or national defense. The research method employed is a normative legal approach, utilizing both a statutory approach and a conceptual approach. The research results indicate that the success of environmental management is highly dependent on law enforcement, coordination among institutions, and active community participation. At the local level, the Depok City Environmental Agency plays a strategic role in formulating and implementing environmental policies, making synergy between national laws and local implementation the key to successful environmental conservation.